Templated synthesis of nano-sized silica in confined amorphous space of polypropylene. (1st March 2017) - Takeuchi, Kengo; Maira, Bulbul; Terano, Minoru; Taniike, Toshiaki
Abstract: A template method is a powerful technique to tailor the morphology of formed nanomaterials. The present paper for the first time demonstrated the sol-gel reaction templated by the higher-order structure of semi-crystalline polymer. Silicon alkoxide was impregnated into the amorphous space of polypropylene (PP) with the aid of supercritical CO2, and subsequently converted into uniformly dispersed silica nanoparticles. The size and anisotropy of silica nanoparticles were controlled through the amorphous thickness of PP that was preliminarily defined through the crystallization process. We also studied the impact of the silica morphology on physical properties of resultant PP/silica nanocomposites. The silica morphology was systematically varied, keeping relatively uniform dispersion. We revealed that the storage modulus of the nanocomposites was well correlated with the size and anisotropy of the nanoparticles.